Characteristics Of Anorectal Malformation Patients - Ummu M Qinayah; Reeny Purnamasari; Jusli, Jusli (Jurnal EduHealth, 2024)
Anorectal malformations represent a broad spectrum of abnormalities in the formation of the anus and rectum ranging from stenosis to anorectal agenesis. The mortality rate of patients with high anorectal malformations is higher than that of low anorectal malformations due to the higher incidence of comorbidities in high anorectal malformations. The incidence of anorectal malformations is still relatively low, while the characteristics of anorectal malformations based on classification, gender, age, birth weight... The method used is literature review with Narrative Review design. The results obtained in this literature are that there are 15 articles obtained with restrictions from 2018 - 2023 and in-depth analysis of the strengths and limitations of each article regarding the incidence and characteristics of anorectal malformations, 12 articles mention the incidence and characteristics of anorectal malformations and 3 articles only mention the incidence of anorectal malformations.